2003 International Symposium on Empirical Software Engineering, 2003. ISESE 2003. Proceedings.
DOI: 10.1109/isese.2003.1237977
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of the variation in effectiveness for DC, FPC and MC/DC test criteria

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The size of the test suite is also comparable to BOR. Reported [8] that average effectiveness of MC/DC remains constant even with increase in number of conditions. MI and MUMCUT does not any restriction on number of variable and number of occurrences of the variables It has been shown [35] that MUMCUT detects all faults detected by MI and the test generated is a subset of test sets generated by MI and the size of test suit is much smaller.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the test suite is also comparable to BOR. Reported [8] that average effectiveness of MC/DC remains constant even with increase in number of conditions. MI and MUMCUT does not any restriction on number of variable and number of occurrences of the variables It has been shown [35] that MUMCUT detects all faults detected by MI and the test generated is a subset of test sets generated by MI and the size of test suit is much smaller.…”
Section: Discussionmentioning
confidence: 99%
“…Boolean expressions from literature ranging from 3 variables to 12 variables used for assessing the, performance and effectiveness of the various testing techniques based on mutation analysis. Mutants were generated for operator fault (ORF,ENF,VNF,ASF) and operand fault (MVF,VRF,CCF,CDF,SA0,SA1 [8] that average effectiveness of MC/DC remains constant even with increase in number of conditions. One approach to overcome the weakness of these is to combine these techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical evaluation of testing technique for Boolean specifications were studied in [8,9,11,13] has explored the relationship between various fault types. It is shown that ENF are weakest faults in the sense that any technique which catches stronger faults are likely to find ENF's.…”
Section: Fault Classesmentioning
confidence: 99%
“…Another aspect for using structural code coverage metrics for the evaluation of the testing effort is the fact that the test set depends on the structure of the code, as shown in [20] In [21] different code coverage metrics (decision coverage, full predicate coverage, and MC/DC) are compared regarding their effectiveness in finding errors. One result of this work is that, in general, the MC/DC criterion was found to be effective [for detecting faults] independent of the number of conditions in the Boolean decision.…”
Section: ---T Ft --T Fft -T Ffftt}mentioning
confidence: 99%